Recipes for improper ferroelectricity in molecular perovskites - Hanna L. B. Boström (Nature Portfolio, 2018)
In layered inorganic materials lattice distortions can couple to break inversion symmetry and drive improper ferroelectricity, but in perovskites, symmetry prohibits such an effect. Here, the authors use group-theoretical analysis to provide crystal engineering design principles for improper ferroelectricity in molecular perovskites.